2010
DOI: 10.1111/j.1469-8986.2010.01024.x
|View full text |Cite
|
Sign up to set email alerts
|

New P300-based protocol to detect concealed information: Resistance to mental countermeasures against only half the irrelevant stimuli and a possible ERP indicator of countermeasures

Abstract: Here, a rare probe or frequent irrelevant stimulus (S1) appeared in the first part of the trial, followed by either a target or nontarget (S2) in the second. Subjects randomly pressed one of five buttons to S1 to signal seeing it. Then they pressed one of two buttons for nontargets or targets. We tested three groups: simple guilty (SG), in which one stimulus was the subject's birth date (Probe); innocent (IN) in which all date stimuli were irrelevant; and Countermeasure (CM), like SG but subjects performed men… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
61
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(68 citation statements)
references
References 14 publications
7
61
0
Order By: Relevance
“…(Brain fingerprinting standards 4-7, 14, 15, and 17. ) This error and its consequences are illustrated by a series of experiments conducted by colleagues (see Farwell 2011a, b, 2012;Lui and Rosenfeld 2008;Johnson and Rosenfeld 1992;Rosenfeld et al 1987Rosenfeld et al , 1988Rosenfeld et al , 1991Rosenfeld et al , 2004Rosenfeld et al , 2006. All of Rosenfeld and colleagues' studies failed to meet 12-17 of the 20 brain fingerprinting standards, including standards 14, 15, and 17 in every case (see Farwell 2011aFarwell , b, 2012.…”
Section: Non-brain Fingerprinting Research On Brainwave-based Concealmentioning
confidence: 99%
See 2 more Smart Citations
“…(Brain fingerprinting standards 4-7, 14, 15, and 17. ) This error and its consequences are illustrated by a series of experiments conducted by colleagues (see Farwell 2011a, b, 2012;Lui and Rosenfeld 2008;Johnson and Rosenfeld 1992;Rosenfeld et al 1987Rosenfeld et al , 1988Rosenfeld et al , 1991Rosenfeld et al , 2004Rosenfeld et al , 2006. All of Rosenfeld and colleagues' studies failed to meet 12-17 of the 20 brain fingerprinting standards, including standards 14, 15, and 17 in every case (see Farwell 2011aFarwell , b, 2012.…”
Section: Non-brain Fingerprinting Research On Brainwave-based Concealmentioning
confidence: 99%
“…One fundamental error that Rosenfeld and a number of other researchers have made is to instruct subjects to ''lie'' in response to probe items in a laboratory experiment (see Farwell 2011aFarwell , b, 2012Rosenfeld et al 1987Rosenfeld et al , 1988Rosenfeld et al , 2004Rosenfeld 2002). Recall that in brain fingerprinting the subject is instructed to press one button in response to targets, and another button in response to all other stimuli.…”
Section: Non-brain Fingerprinting Research On Brainwave-based Concealmentioning
confidence: 99%
See 1 more Smart Citation
“…Grand average ERPs at Pz for each group in both conditions. A. Osugi, H. Ohira Psychology and the researchers limited their analysis to this region (Rosenfeld, Shue, & Singer, 2007;Rosenfeld & Labkovsky, 2010). Therefore, we calculated the largest positive peak in the range of 200 -700 ms at Pz.…”
Section: Erp Datamentioning
confidence: 99%
“…As prominent positive waves were found in both the High and Low Arousal groups, mainly in the supraliminal condition, we investigated this component as the P300 using the peak-amplitude method (see Osugi & Ohira (under review), for the same analysis). Several previous studies investigated the P300 at Pz using the peak-peak (p-p) method, which computes the difference between the P300 peak and the bottom peak from the beginning of the P300 latency to approximately 1300 ms after stimulus onset, and reported that the P300-based CIT method was effective (e.g., Soskins, Rosenfeld, & Niendam, 2001;Rosenfeld & Labkovsky, 2010;Rosenfeld, 2011). However, in the present study we used the peak-amplitude method, because the clear negative peaks that are usually obtained following P300 peaks in P300-based CIT studies were not observed.…”
Section: Erp Datamentioning
confidence: 99%